PENGARUH TAX AWARENESS TAX MORALE DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA YOGYAKARTA - Ade Asriny Y Tanggu; Sri Ayem; Teguh Erawati (Universitas Muhammadiyah Makassar, 2021)
This study aims to examine whether Tax Awareness (Taxpayer Awareness), Tax Morale and Tax Sanctions Influence on taxpayer compliance of micro, small and medium enterprises. The population in this study is Micro, Small and Medium Enterprises in the city of Yogyakarta. The sampling technique in this study used convenience sampling. Data collection is done by distributing questionnaires in the form of google form through the WhatsApp application to respondents. The number of questionnaires that were processed were 62 questionnaires, from google form. Data were analyzed using multiple linear regression analysis. The results of this study indicate that Tax Awareness (taxpayer awareness), Tax Morale and tax sanctions have a positive and significant effect on taxpayer compliance.